2022
DOI: 10.1155/2022/7408136
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Histone Deacetylase9 Represents the Epigenetic Promotion of M1 Macrophage Polarization and Inflammatory Response via TLR4 Regulation

Abstract: Atherosclerosis is a chronic inflammatory response mediated by various factors, where epigenetic regulation involving histone deacetylation is envisaged to modulate the expression of related proteins by regulating the binding of transcription factors to DNA, thereby influencing the development of atherosclerosis. The mechanism of atherosclerosis by histone deacetylation is partly known; hence, this project aimed at investigating the role of histone deacetylase 9 (HDAC9) in atherosclerosis. For this purpose, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%